Analisis Minat Pemilih Mahasiswa Gen Z di Universitas Mataram Terhadap Pemilihan Gubernur Di NTB Tahun 2024 - Amini, Elsa; Fauzi, Meilinda; Ramdhani, Triana Putri; Ulfaturrahmi, Ulfaturrahmi; Putri, Dina Eka; Baskara, Zulhan Widya; Zulhan Widya Baskara (Semeton Mathematics Journal, 2025)
This study aims to analyze the determinants of voting behavior among Generation Z students in the context of the 2024 Gubernatorial Election in West Nusa Tenggara (NTB), Indonesia. Utilizing a quantitative approach, the research applies multiple linear regression to examine the influence of sociological, psychological, and rational factors on voting behavior. Primary data were collected through an online questionnaire distributed to 97 purposively selected active students at the University of Mataram. The instrument employed a 4-point Likert scale to minimize neutral responses. The findings reveal that psychological and rational factors significantly influence voting behavior, whereas sociological factors do not show a statistically significant effect. The regression model yielded an Adjusted R² value of 0.549, indicating that the three independent variables explain 54.9% of the variance in voting behavior.